Investigation of Structural and Thermal Evolution in Novel Layered Perovskite NdSrMn2O5+δ via Neutron Powder Diffraction and Thermogravimetric Analysis. (29th November 2020) - Afroze, Shammya; Yilmaz, Duygu; Reza, Md Sumon; Henry, Paul F.; Cheok, Quentin; Zaini, Juliana H; Azad, Abul K.; Issakhov, Alibek; Sadeghzadeh, Milad
Abstract : Neutron diffraction is one of the best methods for structural analysis of a complex, layered perovskite material with low symmetry by accurately detecting the oxygen positions through octahedral tilting. In this research, the crystal structure of NdSrMn2 O5+ δ was identified through X-ray diffraction (XRD) and neutron powder diffraction (NPD) at room temperature (RT), which indicated the formation of a layered structure in orthorhombic symmetry in the Pmmm (no. 47) space group. Rietveld refinement of the neutron diffraction data has confirmed the orthorhombic symmetry with unit cell parameters ( a  = 3.8367 (1) Å, b  = 3.8643 (2) Å, and c  = 7.7126 (1) Å), atomic positions, and oxygen occupancy. Thermogravimetric analysis revealed the total weight loss of about 0.10% for 20–950°C temperature, which occurred mainly to create oxygen vacancies at high temperatures. Rietveld analyses concurred with the XRD and neutron data allowing correlation of occupancy factors of the oxygen sites.